Pouk slovenščine kot tujega jezika - Črnivec, Ljubica (Jezik in slovstvo, 1997)
The article presents a model of teaching unit which was tested in 1990 in Slovene language classes in Germany. The unit consists of 6 double pages (illustrations and language models) of material for the students, as well as a teacher' manual with ideas on how to apply the material in the calssroom.
Keywords: Slovene; slovenščina; pouk; didactic method; didaktika; metodika; materinščina; first language; tuji jeziki; izseljenci; Nemčija; Germany